Why mountains matter for biodiversity. (11th November 2019) - Perrigo, Allison; Hoorn, Carina; Antonelli, Alexandre
Abstract: Mountains are arguably Earth's most striking features. They play a major role in determining global and regional climates, are the source of most rivers, act as cradles, barriers and bridges for species, and are crucial for the survival and sustainability of many human societies. The complexity of mountains is tightly associated with high biodiversity, but the processes underlying this association are poorly known. Solving this puzzle requires researchers to generate more primary data, and better integrate available geological and climatic data into biological models of diversity and evolution. In this perspective, we highlight emerging insights, which stress the importance of mountain building through time as a generator and reservoir of biodiversity. We also discuss recently proposed parallels between surface uplift, habitat formation and species diversification. We exemplify these links and discuss other factors, such as Quaternary climatic variations, which may have obscured some mountain‐building evidence due to erosion and other processes. Biological evolution is complex and the build‐up of mountains is certainly not the only explanation, but biological and geological processes are probably more intertwined than many of us realize. The overall conclusion is that geology sets the stage for speciation, where ecological interactions, adaptive and non‐adaptive radiations and stochastic processes act together to increase biodiversity. Further integration of these fields may yield novel and robust insights.